The mite fauna of Eksisu Marshes in Erzincan (Turkey) - Dogan, Salih; Sevsay, Sevgi; Ayyildiz, Nusret; Ozbek, Hasan Huseyin; Dilkaraoglu, Sibel; Erman, Orhan; Aksoy, Hakan (Tubitak Scientific & Technological Research Council Turkey, 2015)
Reedbeds can be characterized as forming a transition between the aquatic and terrestrial ecosystems. They have distinctive animals adapted to living in aqueous conditions. Because of the lack of data on the mite fauna in marsh habitats of Turkey, this faunistic study was conducted in the Eksisu Marshes, which resulted in collecting and determining 58 species and 36 genera belonging to 29 families. Of these, Stigmaeus sphagneti (Hull), Neothrombium neglectum (Bruyant), Podothrombium macrocarpum Berlese, Johnstoniana eximia (Berlese), Calyptostomata velutinus (Muller), Heminothrus humicola (Forsslund), Astegistes pilosus (Koch), Achipteria coleoptrata (Linnaeus), and Lauritzenia elegans (Kunst) are new records for the Turkish fauna. The diagnostic features and distributions throughout the world of the species that were determined as newly recorded for Turkey are given. This is also the first report of the families Calyptostomatidae and Neothrombidiidae from Turkey.
Keywords: Mite; fauna; new records; Eksisu Marshes; Erzincan; Turkey